KINERJA KEUANGAN DAN ALOKASI BELANJA MODAL (Studi pada Kabupaten/Kota di Provinsi Aceh) - Lilis Marlina, Mirna Indriani, Heru Fahlevi (Jurnal Akuntansi, 2017)
Abstract: The objective of this study is to examine the effect of financial performance (i.e the degree of decentralization, local dependency, financial independence,  PAD effectiveness) on capital expenditure allocation. The population used in this study is 23 local government district/urban in the Aceh Province with the observation period of 5 years (2010-2014). The analytical method used in this research is the analysis of multiple linear regression with panel data model. The data analysis begins with  descriptive statistics of variable , test selection of panel data regression model, and hypothesis testing. The results of this study show that:(1) financial performance (i.e the of the degree of decentralization, local dependency, financial independence, effectiveness PAD) have simultaneous effect on capital expenditures allocation, (2) financial performance  i.e of the degree of decentralization had affect on capital expenditure allocation, (3) financial performance i.e local dependency had effect on capital expenditure allocation, (4)financial performance i.e financial independence had affect on capital expenditures allocation, (5) financial performance i.e of the PAD effectiveness had effect on  capital expenditure allocation.Keywords : Financial performance, financial ratio, and capital expenditure Abstrak: Penelitian ini bertujuan untuk menguji pengaruh kinerja keuangan (berupa derajat desentralisasi, ketergantungan daerah, kemandirian keuangan, efektivitas PAD) terhadap alokasi belanja modal. Populasi yang digunakan dalam penelitian ini adalah 23 pemerintah daerah kabupaten/kota di Provinsi Aceh dengan periode pengamatan 5 tahun (2010-2014). Metode analisis yang digunakan dalam penelitian ini adalah analisis  regresi  linear berganda dengan model data panel. Hasil penelitian menunjukkan bahwa: (1) kinerja keuangan (berupa dari derajat desentralisasi, ketergantungan daerah, kemandirian keuangan, efektivitas PAD) secara bersama-sama berpengaruh terhadap alokasi belanja modal, (2) kinerja keuangan berupa derajat desentralisasi berpengaruh terhadap alokasi belanja modal, (3) kinerja keuangan berupa ketergantungan daerah berpengaruh  terhadap alokasi belanja modal, (4) kinerja keuangan berupa kemandirian keuangan berpengaruh terhadap alokasi belanja modal, (5) kinerja keuangan berupa efektivitas PAD berpengaruh  terhadap alokasi belanja modal.Kata kunci : Kinerja keuangan, rasio keuangan , dan belanja modal